Problems of youth media of Kazakhstan (Herald of Journalism, 2020)
The article is devoted to the study of the peculiarities of the development of domestic youth publica- tions. The relevance of the topic is determined by their lack of study and special importance for ensuring a stable future of the country, the implementation of the intellectual and creative potential of the younger generation. The purpose of the work is to study the problems of youth mass media in Kazakhstan. The work is aimed at studying the difficult issues of creating Newspapers and magazines for teenagers and young people, as well as their reception, because the needs of the target audience have changed signifi- cantly in recent years.The scientific and practical significance of the work is due to the need to model the prospects for the development of youth publications, improve journalistic skills and media literacy of the target audience. The research methods were monitoring the functioning of youth mass media, analysis of their con- tent, design, and statistical method (sociological survey). The methodological basis of the research wasthe articles of foreign and domestic scientists on the topic.The study material has led to the following results: most popular among young people have zines, the demand for paper publications and television products, low interest in entertainment content on the themes of “star” of life, gender relations, psychology and education, low readability materials about poli- tics. Analysis of this situation reveals the following reasons: lack of competition in the market, insufficient creative approach to design, low level of media literacy of the audience.The study allowed us to systematize the problems of Kazakhstan’s journalism for young people: lack of funding, lack of young talented journalists, low circulation, thematic limitations, competition with foreign publications, high prices, too large advertising blocks, growth of entertainment content, decrease in reader interest.The results of the work are of practical importance for developing a strategy to improve the situation in modern youth media to ensure their participation in shaping the worldview of young people.
Keywords: youth, youth media, social networks, media literacy, decrease in reader interest.